A Preliminary Survey on Functional Programming - Leijen, Daan (2010)
Functional programming has had a profound impact on the development of mainstream languages such as C# or Java. We wanted to get a better sense of developer’s perceptions of functional programming, and also better understand which functional programming concepts are useful to developers. This paper reports the results of a preliminary survey on this topic.